THE INFLUENCE OF THE RATEL INFANTRY FIGHTING VEHICLE ON MOBILE WARFARE IN SOUTHERN AFRICA - de Vries, Roland (Scientia Militaria - South African Journal of Military Studies, 2015)
This article traces the story of how the author and a number of daring young commanders and soldiers had cast aside military textbooks in developing their own military doctrine for mobile warfare, South African style. It is clear that the Ratel infantry fighting vehicle had wielded huge influence on the development and deployment of doctrine for mobile warfare during the 23-year long South African Border War. The author answers a simple ‘yes’, to the question raised whether the military doctrine the South African Defence Force (SADF) had devised during the Border War had served its purpose. He furthermore emphasises that significant lessons can be learned from the way the SADF had fought its military campaigns, a statement borne out by various authoritative publications recently circulated.